1996
DOI: 10.1002/hep.510240616
|View full text |Cite
|
Sign up to set email alerts
|

Differential recognition of the 52-kd Ro(SS-A) antigen by sera from patients with primary biliary cirrhosis and primary Sjogren's syndrome

Abstract: Antibodies against the 52‐kd Ro(SS‐A) protein are significantly associated with the primary Sjogren's syndrome (pSS). A small proportion of patients suffering from primary biliary cirrhosis (PBC) with secondary Sjogren's syndrome (PBC/SS) who are serologically characterized by antimitochondrial type 2 antibodies also express anti‐52‐kd Ro(SS‐A) antibodies. The primary B‐cell‐derived antigenic responses by autoimmune sera were analyzed in both entities using truncated recombinant proteins to examine whether dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The CC domain is the most commonly targeted region of the Ro52 irrespective of the underlying disease, while SS patients seem to have specificities against several different Ro52 epitopes including the RING, B‐box and CC domains . In PBC, a small Ro52 epitope at CC domain (aa228‐245) has been identified as dominant using different fusion proteins in ELISA and immunoblotting .…”
Section: Discussionmentioning
confidence: 99%
“…The CC domain is the most commonly targeted region of the Ro52 irrespective of the underlying disease, while SS patients seem to have specificities against several different Ro52 epitopes including the RING, B‐box and CC domains . In PBC, a small Ro52 epitope at CC domain (aa228‐245) has been identified as dominant using different fusion proteins in ELISA and immunoblotting .…”
Section: Discussionmentioning
confidence: 99%
“…As far as anti‐SS‐A/Ro‐52kD antibodies are concerned, it has been reported that those found in PBC differ from those occurring in primary SS in two aspects: (i) recognition of distinct epitopes within the target molecule; (ii) rate of association with anti‐SS‐B/La antibodies, much lower in PBC 20 . In the present study, anti‐SS‐A/Ro‐52kD and anti‐SS‐B/La were simultaneously detected in PBC at a significantly lower frequency than SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies provided evidence that this mRNA is expressed in fetal but not adult hearts. On the other hand, a variety of studies have shown that the leucine zipper represents the major autoantigenic epitope of this protein [19][20][21][22][23][24][25][26]. Therefore, it raises the question to which degree alternative splicing products play a significant immunopathogenic role.…”
Section: Immunopathogenic Aspectsmentioning
confidence: 99%